Using computer‐based instruction to teach implementation of behavioral skills training. Issue 1 (28th November 2022) - Campanaro, Alexandra M.; Vladescu, Jason C.; DeBar, Ruth M.; Deshais, Meghan A.; Manente, Christopher J.
Abstract : Behavioral skills training (BST) is considered one of the most effective staff training techniques to implement a wide variety of behavioral technologies; however, research has found a lack of implementation of BST across human service settings due to a shortage of organizational time and resources. The purpose of the present study was first to demonstrate the effectiveness of computer‐based instruction (CBI) in teaching BST, and then to demonstrate that the CBI module was effective in training trainers to implement BST with trainees. Results of the present experiment not only demonstrate the effectiveness of CBI in teaching BST, but also demonstrate the generality of the BST to teach behavior therapists.